Ask questions and get helpful answers.

Simplify the trigonometric function

sin^4⁡x-cos^4⁡x
cos^2⁡â-sin^2⁡â=1+2cos⁡â

(1+cot^2⁡x )(cos^2⁡x )=cot^2⁡x

cot^2⁡t/csc⁡t =(1-sin^2⁡t)/sin⁡t (Work on both sides!)
sinècscè- sin^2⁡è=cos^2⁡è

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩
1 answer
  1. sin^4⁡x-cos^4⁡x = (sin^2 x+cos^2 x)(sin^2 x -cos^2 x

    = 1 (sin^2 x - cos^2 x)

    = 2 sin^2 x - 1

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.